Contextual sites of acknowledgement? Kven heritage and contemporary identity articulation processes - Øyen, Gyrid; Kvidal-Røvik, Trine (Acta Borealia, 2023)
It is more than 20 years since Kvens were recognized as a national minority in Norway, yet there is still a need for acknowledgement of Kven culture and heritage. This article discusses contemporary processes of identity articulation related to Kven heritage. Based on interviews with people who relate to a key Kven place in Varanger, we discuss people’s identity articulation processes in different contexts. Specifically, three contextual sites for identity articulation processes are discussed in detail: family, public institutions and discourse, and multicultural society. We maintain that the family site has a pivotal role when it comes to heritage and identity articulation processes, but it can also be a source of pain and struggle. Public discourse and institutions such as media, museums and schools can provide authoritative acknowledgement of identity, but they come with a risk of reducing nuances in identity articulation processes. Within multicultural sites it can be a struggle to find room for people’s ethnic complexities. Across contextual sites, finding support for identity articulation processes is key to acknowledgement of Kven heritage.